2014
DOI: 10.1371/journal.pone.0093405
|View full text |Cite
|
Sign up to set email alerts
|

L-Serine Treatment May Improve Neurorestoration of Rats after Permanent Focal Cerebral Ischemia Potentially Through Improvement of Neurorepair

Abstract: The present study was conducted to clarify whether treatment with L-serine can improve the brain repair and neurorestoration of rats after permanent middle cerebral artery occlusion (pMCAO). After pMCAO, the neurological functions, brain lesion volume, and cortical injury were determined. GDNF, NGF, NCAM L1, tenascin-C, and Nogo-A levels were measured. Proliferation and differentiation of the neural stem cells (NSCs) and proliferation of the microvessels in the ischemic boundary zone of the cortex were evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 50 publications
(66 reference statements)
2
20
0
Order By: Relevance
“…Rats scoring 0, 1, 4 points were excluded from the experiment. Rotarod motor tests 54 55 and Modified Neurological Severity Scores (mNSS) 14 56 57 were performed to evaluate neurological function 1 day before and 1, 3, 7 days after MCAo. The mNSS included tests of motor, sensory, reflex and balance performance with scores ranging from 0 (normal) to 18 (maximal deficit).…”
Section: Methodsmentioning
confidence: 99%
“…Rats scoring 0, 1, 4 points were excluded from the experiment. Rotarod motor tests 54 55 and Modified Neurological Severity Scores (mNSS) 14 56 57 were performed to evaluate neurological function 1 day before and 1, 3, 7 days after MCAo. The mNSS included tests of motor, sensory, reflex and balance performance with scores ranging from 0 (normal) to 18 (maximal deficit).…”
Section: Methodsmentioning
confidence: 99%
“…found that L‐serine infusion reduced the infarct volume in a mouse MCAO model, and they speculated that this action of L‐serine may be dependent on a vasodilatory effect, since L‐serine increases cerebral blood flow . Furthermore, a neuro‐restorative role of L‐serine, in addition to its neuroprotective role, has been postulated …”
Section: Amino Acid and D‐/l‐serinementioning
confidence: 99%
“…163 Furthermore, a neuro-restorative role of L-serine, in addition to its neuroprotective role, has been postulated. 164…”
Section: Glutamate and Nmda Receptor Co-agonistsmentioning
confidence: 99%
“…L-serine is a non-essential amino acid that exhibits essential functions in the central nervous system, particularly protein synthesis and cell proliferation [28]. For example, treatment with L-serine facilitated the proliferation of NSCs derived from rats with induced brain injury, and pharmacological inhibition of the enzyme serine hydroxymethyltransferase (SHMT) impaired the effects of L-serine on NSC proliferation [29]. SHMT initiates L-serine catabolism in the one-carbon metabolism for purine and pyrimidine synthesis [28], suggesting that L-serine possibly acts on NSPCs through this pathway.…”
Section: Plos Onementioning
confidence: 99%